Future enhanced threshold effects of wildfire drivers could increase burned areas in northern mid- and high latitudes - Hang Zhao; Zhengxiang Zhang; Xin Wang; Shuo Zhen; Hongyan Zhang; Zhao-Jun Bu; Jianjun Zhao; Xiaoyi Guo; Kejiang Wei; Long Dong (Communications Earth & Environment)
Abstract Wildfires exhibit extensive nonlinear characteristics and threshold effects in response to environmental changes. However, how threshold effects affect wildfire responses and their future changes remains unclear. Here we identified thresholds where wildfire-driver relationships shift and estimated the impact of threshold effects on wildfire dynamics in the 21st century in northern mid- and high latitudes (>30°N). Wildfire-driver thresholds, coregulated by gradient differences in heat and moisture conditions, vegetation productivity, and human activities, effectively explain the spatial patterns and uneven responses of wildfires. Despite the dominance of temperature, precipitation, and socioeconomic status on wildfires, 30.70% of wildfire changes are attributed to their threshold effects, notably in boreal and temperate ecosystems. Climate change will enhance the threshold effects of wildfire drivers, leading to a 47.81 ± 3.08% increase in burned areas by 2030–2100 compared with 2001‒2022. Our findings highlight that enhanced threshold effects of drivers promote future wildfire changes, posing challenges to fire suppression.